Molecular genetics and phenotypic assessment of foxtail millet (Setaria italica (L.) P. Beauv.) landraces revealed remarkable variability of morpho-physiological, yield, and yield‐related traits - Ramesh, Palakurthi; Juturu, Vijaya Naresh; Yugandhar, Poli; Pedersen, Sydney; Hemasundar, Alavilli; Yolcu, Seher; Chandra Obul Reddy, Puli; Chandra Mohan Reddy, C. V.; Veerabramha Chari, P.; Mohan, Rajinikanth; Chandra Sekhar, Akila (Frontiers in Genetics, 2023)
Foxtail millet (Setaria italica L.) is highly valued for nutritional traits, stress tolerance and sustainability in resource-poor dryland agriculture. However, the low productivity of this crop in semi-arid regions of Southern India, is further threatened by climate stress. To explore the genetic diversity, to identify novel alleles and to identify superior genotypes, we collected a heterogeneous mixture of foxtail millet landraces from farmer fields. In an extensive multi-year study, we developed twenty genetically fixed foxtail millet landraces by single seed descent method and evaluated their yield, morpho-physiological and yield-related traits along with four released cultivars. The landraces showed significant diversity in days to flowering and maturity and panicle characteristics and other agronomical traits. We identified landraces S3G5, Red, Black and S1C1 that showed outstanding grain yield and earlier flowering, and maturity compared to released cultivars. Diversity analysis using 67 simple sequence repeat microsatellite and other markers detected 127 alleles including 11 rare alleles, averaging 1.89 alleles per locus, expected heterozygosity of 0.26 and an average polymorphism information content (PIC) of 0.23, collectively indicating a moderate genetic diversity in the landrace populations. Euclidean Ward’s clustering, based on the markers, principal coordinate analysis (PCoA) and Structure analysis concordantly distinguished the genotypes into 2-3 sub-populations. A significant phenotypic and genotypic diversity observed in the landraces indicates a diverse gene pool that can be utilized for sustainable foxtail millet crop improvement.